2018
DOI: 10.1124/jpet.117.247171
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Parkinsonian Primates in Pharmacologic Studies: A Comparison between the Macaque, Marmoset, and Squirrel Monkey

Abstract: The 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned primate is the gold-standard animal model of Parkinson disease (PD) and has been used to assess the effectiveness of experimental drugs on dyskinesia, parkinsonism, and psychosis. Three species have been used in most studies-the macaque, marmoset, and squirrel monkey-the last much less so than the first two species; however, the predictive value of each species at forecasting clinical efficacy, or lack thereof, is poorly documented. Here, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 399 publications
0
5
0
Order By: Relevance
“…We undertook the current study to investigate whether nelotanserin would alleviate L‐DOPA‐induced dyskinesia in the MPTP‐lesioned marmoset to provide incremental evidence of 5‐HT 2A antagonism/inverse agonism as an effective anti‐dyskinetic approach. As the marmoset has high predictive value of the efficacy of drugs at the phase II level (Beaudry & Huot, 2020; Veyres et al, 2018), if nelotanserin is demonstrated to be an efficacious anti‐dyskinetic molecule in this animal model of PD, it could conceivably be repurposed for the treatment of drug‐induced dyskinesia.…”
Section: Introductionmentioning
confidence: 99%
“…We undertook the current study to investigate whether nelotanserin would alleviate L‐DOPA‐induced dyskinesia in the MPTP‐lesioned marmoset to provide incremental evidence of 5‐HT 2A antagonism/inverse agonism as an effective anti‐dyskinetic approach. As the marmoset has high predictive value of the efficacy of drugs at the phase II level (Beaudry & Huot, 2020; Veyres et al, 2018), if nelotanserin is demonstrated to be an efficacious anti‐dyskinetic molecule in this animal model of PD, it could conceivably be repurposed for the treatment of drug‐induced dyskinesia.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, marmosets have been more frequently used in preclinical, toxicology, and safety assessment of drugs. 4-30…”
Section: Introductionmentioning
confidence: 99%
“…The capture of the multifactorial nature of PD is often difficult in cellular or animal models. The 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned non-human primate remains the gold-standard animal model of PD and is frequently used to evaluate the effectiveness of molecules on parkinsonism and psychosis ( Veyres et al, 2018 ). Higher MPTP dose can lead to acute dopaminergic cell loss within 1 month, while low dose usually takes 8-12 months to achieve stable parkinsonism ( Bezard et al, 2001 ; Seo et al, 2019 ; Barth et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%